Utilization of Plastic Waste (HDPE, PET, and PP) For Paving Block Mixture Materials - Ihsan Abadi; BP Samadikun; HS Huboyo (Journal Research of Social Science, Economics, and Management, 2026)
Waste has always been a major problem in the environment due to the lack of public knowledge in waste management. One type of waste commonly generated by people daily is plastic waste. One of the efforts that can be made to utilize plastic waste is to incorporate it as a mixture material in the production of paving blocks. The purpose of this study is to compare the mechanical properties of paving blocks for each type of plastic used, both in terms of compressive strength and water absorption. The methods employed include data collection and analysis, as well as laboratory testing. The findings indicate that HDPE plastic exhibits the highest compressive strength among the three types, while PP plastic shows the best water absorption performance, with HDPE also demonstrating favorable absorption characteristics. These results imply that plastic waste, particularly HDPE, can be effectively utilized as a sustainable alternative material in non-structural construction applications such as paving blocks, contributing to waste reduction efforts and promoting environmentally friendly construction practices. Thus, it is hoped that this research can serve as a reference in the processing of plastic waste in the fields of both architecture and environmental engineering.